Lead-free piezoelectric composition and piezoelectric element

JP2025021632APending Publication Date: 2025-02-14NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023125466
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、製造時の燒結温度が低く抑えられた無鉛圧電組成物等を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021632000006
    Figure 2025021632000006
  • Figure 2025021632000007
    Figure 2025021632000007
  • Figure 2025021632000008
    Figure 2025021632000008
Patent Text Reader

Abstract

To provide a lead-free piezoelectric composition or the like having a low sintering temperature during production.SOLUTION: A lead-free piezoelectric composition has a main phase formed of a first crystal phase composed of an alkali niobate-based perovskite oxide and a sub-phase containing a second crystal phase composed of a M-Ti-O spinel compound (element M is a 1-4 valent metal element). The alkali niobate-based perovskite oxide is represented by the following composition formula (1). (KaNabLicCadCe)f(DgEh)Oi...(1) where element C is at least one of Sr and Ba, element D is at least one of Nb, Ti and Zr but having at least Nb, element E is at least one of Fe, Co and Zn, a+b+c+d+e=1, 0.004≤d≤0.020, f is any value, g+h=1, and i is any value capable of maintaining a perovskite crystal structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lead-free piezoelectric composition and a piezoelectric element. [Background technology]

[0002] Conventionally, most piezoelectric elements have been made of PZT (lead zirconate titanate)-based materials. However, the lead contained in PZT is viewed as a problem because it causes environmental load, and in recent years, development of piezoelectric elements made of lead-free materials has been progressing.

[0003] As this type of lead-free material, for example, a lead-free piezoelectric composition has been proposed that has a main phase formed of a first crystal phase made of an alkali niobate-based perovskite oxide and a subphase containing a second crystal made of an M-Ti-O-based spinel compound (element M is a monovalent to tetravalent metal element) (see Patent Document 1).

[0004] Although the alkali niobate perovskite oxide constituting the main phase is originally a material that is prone to the formation of voids that cause a decrease in piezoelectric properties, the structure of the main phase (first crystal phase) is stabilized by filling the voids in the main phase with a subphase containing a second crystal. Therefore, the lead-free piezoelectric composition has excellent piezoelectric properties. When force is applied to such a lead-free piezoelectric composition, a voltage is generated, and when a voltage is applied, the lead-free piezoelectric composition expands and contracts in dimensions and changes in shape. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 156015 Summary of the Invention [Problem to be solved by the invention]

[0006] Although the above-mentioned lead-free piezoelectric composition has excellent piezoelectric properties, there is a problem in that the sintering temperature during production is relatively high (e.g., 1100°C or higher). For example, when such a lead-free piezoelectric composition is used to produce a piezoelectric element, the material usable for the electrodes of the piezoelectric element is limited to a metal material with a high melting point (e.g., platinum). Such metal materials are generally valuable and expensive, so it has been desired to reduce the amount of them used from the viewpoint of cost reduction, etc.

[0007] An object of the present invention is to provide a lead-free piezoelectric composition and the like which can be produced at a low sintering temperature. [Means for solving the problem]

[0008] The means for solving the above problems are as follows. <1> A lead-free piezoelectric composition having a main phase formed of a first crystal phase made of an alkali niobate-based perovskite oxide and a subphase including a second crystal phase made of an M-Ti-O-based spinel compound (element M is a monovalent to tetravalent metal element), wherein the alkali niobate-based perovskite oxide is represented by the following composition formula (1): (K a Na b Li c Ca d C e ) f (D g E h )O i ...(1) However, element C is at least one of Sr and Ba, element D is at least one of Nb, Ti, and Zr including at least Nb, element E is at least one of Fe, Co, and Zn, a+b+c+d+e=1, 0.004≦d≦0.020, f is an arbitrary value, g+h=1, and i is an arbitrary value that can maintain a perovskite crystal structure.

[0009] <2> r, which is the D50 value of the particle size distribution of the first crystal phase 50 [μm] is 0.57 or more <1> The lead-free piezoelectric composition according to claim 1.

[0010] <3> The specific gravity is 4.4 or more. <1> or <2> The lead-free piezoelectric composition according to claim 1.

[0011] <4> The above <1> ~ <3> 1. A piezoelectric element having a structure in which the lead-free piezoelectric composition according to any one of 1 to 8 and electrodes are alternately laminated. Effect of the Invention

[0012] According to the present invention, it is possible to provide a lead-free piezoelectric composition and the like in which the sintering temperature during production is kept low. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a perspective view of a piezoelectric element according to a first embodiment; [Diagram 2] 1 is a cross-sectional view of a piezoelectric element according to a second embodiment. [Diagram 3] Graph summarizing the results of the piezoelectric constant and specific gravity of Examples 1 to 3 and Comparative Examples 1 and 2 [Figure 4] Graph summarizing the results of the piezoelectric constant and specific gravity of Examples 2, 7, and 8. [Diagram 5] Graph summarizing the results of the piezoelectric constant and specific gravity of Comparative Examples 2 to 4 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The lead-free piezoelectric composition and the piezoelectric element according to the embodiment will be described below.

[0015] The lead-free piezoelectric composition has a major phase formed of a first crystal phase made of an alkali niobate-based perovskite oxide and a minor phase including a second crystal phase made of an M-Ti-O-based spinel compound.

[0016] In this specification, the term "spinel compound" includes both normal spinel compounds having a normal spinel crystal structure and inverse spinel compounds having an inverse spinel crystal structure. The element M in the M-Ti-O spinel compound is a monovalent to tetravalent metal element.

[0017] The ratio of the second crystal phase in the lead-free piezoelectric composition is more than 0 volume % and not more than 10 volume %, and the remainder is the first crystal phase. In this specification, the first crystal phase is also referred to as the "main phase", and the crystal phase other than the main phase is referred to as the "subphase".

[0018] The alkali niobate perovskite oxide is represented by the following composition formula (1).

[0019] (K a Na b Li c Ca d C e ) f (D g E h )O i ...(1)

[0020] However, element C is at least one of Sr (strontium) and Ba (barium), element D is at least one of Nb (niobium), Ti (titanium), and Zr (zirconium) including at least Nb, and element E is at least one of Fe (iron), Co (cobalt), and Zn (zinc).

[0021] In the above composition formula (1), K (potassium), Na (sodium), Li (lithium), Ca (calcium), and element C are arranged in what is called the A site of the perovskite structure, and elements D and E are arranged in what is called the B site of the perovskite structure.

[0022] The values ​​of the coefficients a, b, c, d, e, f, g, h, and i in the composition formula (1) are those that establish a perovskite structure and are suitable for the electrical or piezoelectric properties of the lead-free piezoelectric composition (particularly the piezoelectric constant d 33 ) and also from the viewpoint of keeping the sintering temperature low during production.

[0023] Specifically, the sum of the coefficients a, b, c, d, and e of the A-site elements is 1 (i.e., a+b+c+d+e=1).

[0024] In particular, the coefficient d of Ca satisfies 0.004 ≤ d ≤ 0.020.

[0025] For the coefficients a, b, and c, it is preferable that 0 ≤ a < 1, 0 ≤ b < 1, and 0 ≤ c < 1, respectively. However, it is preferably not the case that a = b = c = 0 (i.e., a lead-free piezoelectric composition containing neither K, Na, nor Li). The coefficients a and b of K and Na are typically 0 < a ≤ 0.6 and 0 < b ≤ 0.6. The coefficient c of Li may be 0 (zero), but 0 < c ≤ 0.2 is preferable, and 0 < c ≤ 0.1 is more preferable.

[0026] The coefficient e of element C may be 0 (zero), but 0 < e ≤ 0.2 is preferable, and 0 < e ≤ 0.1 is more preferable.

[0027] The coefficient f for the entire A site can be any value as long as the object of the present invention is not impaired. As the coefficient f, 0.80 ≤ f ≤ 1.10 is preferable, 0.84 ≤ f ≤ 1.08 is more preferable, and 0.88 ≤ f ≤ 1.07 is even more preferable.

[0028] The sum of the coefficients g and h of elements D and E at the B site is 1 (i.e., g + h = 1). As long as the object of the present invention is not impaired, the coefficient g of element D is preferably not 0 (zero), and the coefficient h of element E may be 0 (zero).

[0029] The coefficient i of oxygen (O) can be any value that allows the first crystal phase to maintain a perovskite crystal structure. A typical value of the coefficient i is about 3, and 3.0 ≤ i ≤ 3.1 is preferable. The value of the coefficient i can be calculated from the electrical neutrality condition of the composition of the first crystal phase. However, a composition slightly deviating from the electrical neutrality condition is also acceptable as the composition of the first crystal phase.

[0030] Since the alkali niobate perovskite oxide represented by the above composition formula (1) is an oxide having K, Na, and Nb as main metal components, it is referred to as "KNN" or "KNN material". Such an alkali niobate perovskite oxide is excellent in piezoelectric properties, electrical properties, etc.

[0031] The above compositional formula (1) can be rewritten as the following compositional formula (1A).

[0032] (K a Na b Li c Ca d Sr e1 Ba e2 ) f (Nb g1 Ti g2 Zr g3 Fe h1 Co h2 Zn h3 )O i ·····(1A)

[0033] The above compositional formula (1) and compositional formula (1A) are equivalent, where e1 + e2 = e, g1 + g2 + g3 = g, and h1 + h2 + h3 = h.

[0034] The sum of the coefficients a, b, c, d, e1, and e2 is 1 (i.e., a + b + c + d + e1 + e2 = 1). The coefficient e1 of Sr may be 0 (zero), but 0 < e1 ≤ 0.2 is preferred, and 0 < e1 ≤ 0.1 is more preferred. The coefficient e2 of Ba is preferably 0 < e2 ≤ 0.2, and more preferably 0 < e2 ≤ 0.1. Also, the coefficient d is 0.004 ≤ d ≤ 0.020, and the coefficient f is an arbitrary value. The sum of the coefficients g1 of Nb, g2 of Ti, g3 of Zr, h1 of Fe, h2 of Co, and h3 of Zn is 1 (i.e., g1 + g2 + g3 + h1 + h2 + h3 = 1). The coefficient i of oxygen (O) is an arbitrary value that allows the first crystal phase to maintain a perovskite-type crystal structure.

[0035] In the lead-free piezoelectric composition of this embodiment, the value r 50 [μm] of the cumulative 50% particle diameter (D50) based on the number in the particle size distribution of the first crystal phase is preferably 0.57 or more (i.e., r 50 ≥ 0.57), and more preferably 0.68 or more (i.e., r 50 ≥ 0.68). The measurement method of the cumulative 50% particle diameter (D50) based on the number will be described later.

[0036] In addition, the value of D50 is r 50 The upper limit of [μm] is not particularly limited as long as it does not impair the object of the present invention, but from the viewpoint of mechanical strength, for example, it is preferably 1.60 or less.

[0037] Furthermore, in the lead-free piezoelectric composition of the present embodiment, the specific gravity is preferably 4.4 or more, and more preferably 4.5 or more.

[0038] The M-Ti-O spinel compound of the second crystal phase is an oxide containing element M (a monovalent to tetravalent metal element) and Ti (titanium), and is represented, for example, by the following composition formula (2).

[0039] M x TiO y ...(2)

[0040] Here, the element M is a monovalent to tetravalent metal element. Specifically, the element M is at least one element selected from the group consisting of Li, Fe, Co, Zn, and Zr.

[0041] The coefficients x and y are relative values ​​when the Ti content is taken as 1. In order for the second crystal phase to form a spinel compound, it is preferable that the coefficient x satisfies 0.5≦x≦5.0. The coefficient y may be any value that forms a spinel compound, but it is preferable that the coefficient y satisfies, for example, 2≦y≦8.

[0042] The second crystal phase composed of a spinel compound stabilizes the structure of the first crystal phase, so that a lead-free piezoelectric composition having excellent piezoelectric properties can be obtained. From the viewpoint of piezoelectric properties, it is preferable to adopt the second crystal phase represented by the composition formula M2TiO4 or (M1,M2)TiO4 containing two divalent metal elements M.

[0043] The spinel compound forming the second crystal phase may be a normal spinel compound or an inverse spinel compound. Whether the second crystal phase is a spinel compound or not can be determined by performing Rietveld analysis using the diffraction results of powder X-ray diffraction (XRD). The amount of metal elements other than Li in the spinel compound can be analyzed using an electron probe microanalyzer (EPMA) or an energy dispersive X-ray spectrometry (TEM-EDS). The amount of Li can be analyzed using a time-of-flight secondary ion mass spectrometer (TOF-SIMS).

[0044] The second crystal phase does not have piezoelectric properties, but by being mixed with the first crystal phase, it improves the sintering property of the lead-free piezoelectric composition, improves its structural stability, and improves its piezoelectric properties. Specifically, the second crystal phase fills the voids formed between the crystals of the first crystal phase. As a result, the crystals of the first crystal phase are bonded to each other by the second crystal phase, which is presumably why the structural stability of the lead-free piezoelectric composition is improved, and the piezoelectric properties are improved.

[0045] The lead-free piezoelectric composition may contain a crystal phase (such as a third crystal phase) other than the second crystal phase as a subphase, as long as the object of the present invention is not impaired.

[0046] In this embodiment, the proportion of the subphase in the lead-free piezoelectric composition is not particularly limited as long as it does not impair the object of the present invention, but for example, it is preferably more than 0 volume % and not more than 10 volume %, and more preferably 0.5 volume % or more and 5 volume % or less.

[0047] The lead-free piezoelectric composition of the present embodiment may contain elements other than those contained in the first crystal phase and the second crystal phase as inevitable impurities in an amount of 1000 ppm or less.

[0048] In the lead-free piezoelectric composition of this embodiment, the ratio of Ca in the main phase formed of the first crystal phase consisting of the alkali niobate perovskite oxide represented by the above composition formula (1) (the molar ratio of Ca to A site ions) is set to 0.004 or more and 0.02 or less (i.e., 0.004≦d≦0.02), and sintering is possible, for example, by firing at a temperature of 1000°C or less for a predetermined time (for example, 60 hours to 100 hours) during production.

[0049] Therefore, in a piezoelectric element formed using the lead-free piezoelectric composition, it is possible to use a metal material with a relatively low melting point as the electrode material. For example, an AgPd alloy containing 80% or more of Ag can be used as this type of electrode material. Since such an electrode material is not heated to a temperature exceeding 1000°C, melting into islands (so-called island formation) is suppressed.

[0050] Next, a piezoelectric element 200 according to the first embodiment will be described with reference to Fig. 1. Fig. 1 is a perspective view of the piezoelectric element 200 according to the first embodiment. As shown in Fig. 1, the piezoelectric element 200 according to the present embodiment has a disk-shaped appearance and includes a disk-shaped piezoelectric layer (an example of a piezoelectric ceramic layer) 100 and electrodes 301, 302 attached to the upper and lower surfaces of the piezoelectric layer 100. The piezoelectric layer 100 is formed from the above-mentioned lead-free piezoelectric composition. The piezoelectric layer 100 is polarized in the thickness direction. The electrodes 301, 302 are made of, for example, Au or Ag.

[0051] Here, an example of a manufacturing method of the piezoelectric element 200 according to the first embodiment will be described. First, a plurality of kinds of raw material powders necessary for forming the main phase are prepared, and the raw material powders are weighed according to the values ​​of the coefficients a, b, c, d, e, f, g, and h in the composition formula of the main phase so as to obtain a target composition. The raw material powders may be oxides of each element contained in the main phase, carbonates of each element, hydroxides of each element, and the like. Specific raw material powders for the main phase include, for example, K2CO3 powder, Na2CO3 powder, LiCO3 powder, CaCO3 powder, SrCO3 powder, BaCO3, Nb2O5 powder, ZrO2 powder, Fe2O3 powder, CoO powder, and ZnO powder.

[0052] The weighed raw material powders are pulverized and mixed for 4 hours or more using a dry vibration mill to obtain a mixed powder. The obtained slurry is dried, and the mixed powder obtained after drying is calcined, for example, in air at a temperature of 600 to 1000°C for 1 to 10 hours to obtain a powdered calcined main phase product.

[0053] In addition, a plurality of kinds of raw material powders necessary for forming the subphase are prepared, and the raw material powders are weighed according to the value of the coefficient x in the composition formula of the subphase so as to obtain a target composition. The raw material powders may be oxides, carbonates, hydroxides, etc. of each element contained in the subphase. Specific raw material powders for the subphase include, for example, TiO2 powder, ZnO2 powder, Co3O4 powder, Fe2O3 powder, etc. After weighing, each raw material powder is pulverized and mixed for 4 hours or more using a dry vibration mill to obtain a mixed powder. The obtained mixed powder is calcined, for example, in an air atmosphere at a temperature condition of 600 to 1000°C for 1 to 10 hours to obtain a powdered calcined product of the subphase.

[0054] Next, a dispersant, a binder, water, and an antifoaming agent are added to the obtained calcined main phase and subphase products, and the mixture is pulverized and mixed to obtain a slurry. Thereafter, the obtained slurry is dried, and the obtained dried product is appropriately granulated and uniaxially pressed under a pressure condition of, for example, 10 MPa to obtain a disk-shaped compact.

[0055] The obtained molded body is then subjected to a binder removal process by, for example, holding the molded body for 2 to 10 hours at a temperature condition of 200 to 650° C. Then, the molded body after the binder removal process is fired, for example, at a temperature condition of 1000° C. or less in the air atmosphere for 60 to 100 hours to obtain a piezoelectric layer.

[0056] On both front and back surfaces of the obtained piezoelectric layer, electrodes made of Au are formed by, for example, a sputtering method, or electrodes made of Ag are formed by screen printing. Then, the laminate with the electrodes formed on the piezoelectric layer is subjected to a polarization process in which a DC voltage of 3.5 kV / mm is applied in silicone oil at 40° C., thereby expressing the voltage characteristics of the piezoelectric layer. In this way, the piezoelectric element 200 is obtained.

[0057] Next, a piezoelectric element 10 according to a second embodiment will be described with reference to FIG. 2. FIG. 2 is a cross-sectional view of the piezoelectric element 10 according to the second embodiment. As shown in FIG. 2, the piezoelectric element 10 of this embodiment includes a piezoelectric layer (an example of a piezoelectric ceramic layer) 11, a plurality of internal electrodes 12, 13 in contact with the piezoelectric layer 11, and two external electrodes 14, 15 connected to the internal electrodes 12, 13. The piezoelectric layer 11 is formed of the above-mentioned lead-free piezoelectric composition. The internal electrodes 12, 13 are mainly composed of a metal having a relatively low melting point (for example, an AgPd alloy containing 80% or more of Ag). The piezoelectric layer 11 and the internal electrodes 12, 13 are alternately laminated. More specifically, the piezoelectric layer 11 and the internal electrodes 12, 13 are laminated in the order of the piezoelectric layer 11, the internal electrode 12, the piezoelectric layer 11, the internal electrode 13, the piezoelectric layer 11, etc., and one piezoelectric layer 11 is sandwiched between the two internal electrodes 12, 13. The two external electrodes 14, 15 are disposed on the outer surface of a laminate of the piezoelectric layer 11 and the internal electrodes 12, 13. The external electrodes 14, 15 are mainly composed of Ag, for example. One end of one internal electrode 12 of the two internal electrodes 12, 13 in contact with one piezoelectric layer 11 is connected to one external electrode 14, and one end of the other internal electrode 13 is connected to the other external electrode 15. When a voltage is applied between the external electrodes 14, 15, the piezoelectric layer 11 expands and contracts, and the entire piezoelectric element 10 expands and contracts.

[0058] Here, an example of a method for manufacturing the piezoelectric element 10 according to the second embodiment will be described. First, a plurality of kinds of raw material powders necessary for forming the main phase are prepared, and the raw material powders are weighed according to the values ​​of the coefficients a, b, c, d, e, f, g, and h in the composition formula of the main phase so as to obtain a target composition. The raw material powders for the main phase are the same as those in the first embodiment. The weighed raw material powders are pulverized and mixed for 4 hours or more using a dry vibration mill to obtain a mixed powder. The obtained mixed powder is calcined, for example, in an air atmosphere at a temperature condition of 600 to 1000° C. for 1 to 10 hours to obtain a powdered calcined product of the main phase.

[0059] In addition, multiple types of raw material powders necessary for forming the subphase are prepared, and these raw material powders are weighed out according to the value of the coefficient x in the composition formula of the subphase so as to obtain a target composition. The raw material powders for the subphase are the same as those in the first embodiment. The weighed raw material powders are pulverized and mixed for 4 hours or more using a dry vibration mill to obtain a mixed powder. The obtained mixed powder is calcined, for example, in an air atmosphere at a temperature condition of 600 to 1000°C for 1 to 10 hours to obtain a powdered calcined product of the subphase.

[0060] Next, a dispersant, a binder, and an organic solvent (e.g., toluene) are added to the obtained calcined main phase and subphase products, and the mixture is pulverized and mixed to obtain a slurry. After that, the slurry is processed into a sheet shape using a doctor blade method or the like to produce a ceramic green sheet.

[0061] Next, an electrode layer that will become an internal electrode is formed on one side of the ceramic green sheet by, for example, screen printing using a conductive paste for the internal electrodes. The electrode layer is mainly composed of a metal with a relatively low melting point (for example, an AgPd alloy containing 80% or more Ag).

[0062] Then, the ceramic green sheets on which the electrode layers are formed are stacked so that the electrode layers are exposed alternately from both sides, and ceramic green sheets on which no electrode layers are formed are further stacked on both sides of the obtained laminate. The obtained laminate is pressed to obtain a laminate in which the ceramic green sheets and the electrode layers are alternately stacked. The laminate is cut into a desired shape, and then subjected to a binder removal treatment by, for example, maintaining the laminate at a temperature condition of 200 to 650°C for 2 to 10 hours.

[0063] After the binder removal treatment, the laminate is fired, for example, at a temperature of 1000° C. or less in the air for 25 to 40 hours.

[0064] After the side surfaces of the fired laminate are appropriately polished, a pair of external electrodes made of Au are formed on the side surfaces of the laminate by, for example, a sputtering method. The pair of external electrodes are formed facing each other with the laminate between them. The laminate with the external electrodes formed thereon is subjected to a polarization process (see embodiment 1) to obtain a piezoelectric element 10.

[0065] The manufacturing methods of the above-mentioned embodiment 1 and embodiment 2 are both examples, and various other steps and processing conditions for manufacturing a piezoelectric element can be adopted. For example, instead of separately producing the calcined products of the main phase and the subphase and then mixing and firing the powders of both, the raw materials may be mixed in a quantity ratio according to the final composition of the lead-free piezoelectric composition, and the mixture may be fired. However, according to the method of separately producing the calcined products of the main phase and the subphase and then mixing them, the composition of the main phase and the subphase can be more strictly controlled, so that the yield of the lead-free piezoelectric composition can be increased. In addition, metals or alloys such as platinum (Pt), silver-palladium (Ag-Pd), and silver (Ag) may be used as the material of the electrodes.

[0066] The lead-free piezoelectric composition and piezoelectric element disclosed in this specification have excellent piezoelectric properties, a high dielectric breakdown voltage, and excellent insulation properties. Such lead-free piezoelectric composition and piezoelectric element can be widely used for vibration detection, pressure detection, oscillation, piezoelectric device, etc. For example, they can be used in sensors (Knox sensors and combustion pressure sensors, etc.) that detect various vibrations, piezoelectric devices such as vibrators, actuators, and filters, high-voltage generators, micro power sources, various driving devices, position control devices, vibration suppression devices, fluid discharge devices (paint discharge, fuel discharge, etc.), etc. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples in any way.

[0068] Example 1 As raw material powders, Nb2O5 powder, Na2CO3 powder, K2CO3 powder, CaCO3 powder, and Li2CO3 powder were prepared and weighed out so that the coefficients in the composition formula of the first crystal phase were in the quantitative ratios shown in Table 1. After weighing, the weighed out materials were ground and mixed for 4 hours using a dry vibration mill. The mixed powder obtained was then placed in a specified crucible and heated (calcined) at 700°C or higher for 4 hours to obtain primary calcined powder α. Using the same procedure, primary calcined powder β (Nb 1.21 Ti 0.89 K 0.89 O5), and the primary calcined powder γ(BaZrO3) was obtained from the raw material powders ZrO2 powder and BaCO3 powder.

[0069] The obtained primary calcined powder α, primary calcined powder β, primary calcined powder γ, and three additives (ZnO2, CoO4, Fe2O3) were weighed according to the coefficients a, b, c, d, e, f, g, and h in the composition formula of the main phase to obtain the target composition. After weighing, they were ground and mixed for 4 hours using a dry vibration mill. The obtained mixed powder was then placed in a specified crucible and heated (calcined) at 800°C or higher for 4 hours to obtain the secondary calcined powder.

[0070] To the obtained secondary calcined powder, glycerin, binder, antifoaming agent, and water were added in predetermined amounts, and the mixture was pulverized and mixed in a wet ball mill for about 20 hours to obtain a slurry. The slurry was then spray-dried at about 200°C to obtain a granulated powder. The granulated powder was then molded in a press to obtain a disk-shaped compact with a diameter of 24 mm and a thickness of 3 mm. The pressure condition was about 10 MPa, and the green density of the compact was 2.8 g / cm. 3 That was about it.

[0071] The obtained molded body was then degreased by heating at 500°C for 5 hours, and then heated under the conditions of the firing temperature T [°C] and firing time t [hours] shown in Table 1 to obtain a fired body.

[0072] The obtained sintered body was processed by flat grinding to obtain a sintered body with a thickness of 1 mm. Then, Ag electrodes were formed on the surfaces (upper and lower surfaces) of the sintered body with a thickness of 1 mm by screen printing, and the sintered body with the Ag electrodes was baked at 620°C to obtain a test piece. The test piece was subjected to a polarization treatment in which a direct current of 3.5 kV / mm was applied in oil at 40°C.

[0073] [Examples 2 to 8 and Comparative Examples 1 to 4] When preparing the primary calcined powder α, each raw material powder was weighed out so that each coefficient in the composition formula of the first crystal phase had the quantitative ratio shown in Table 1, and the degreased molded body was heated under the conditions of the sintering temperature T [°C] and sintering time t [hours] shown in Table 1. Except for this, the test pieces of Examples 2 to 8 and Comparative Examples 1 to 4 were obtained in the same manner as in Example 1.

[0074] 〔evaluation〕 For each of the test pieces of Examples 1 to 8 and Comparative Examples 1 to 4, various tests shown below were carried out.

[0075] (specific gravity) The specific gravity of the test pieces (i.e., the sintered bodies) before surface polishing was measured by Archimedes' method. The results are shown in Tables 2 to 5.

[0076] (Particle size of the first crystal phase) The surface (polished surface) of the test piece in the flat-polished state was photographed using a JEOL reflective microscope JSM-6390LA, and a field of view of 65 μm × 45 μm was set in the photographed image. Within the field of view, 100 particles (crystal particles) in the first crystal phase were arbitrarily selected using image analysis software. Then, for the selected 100 particles, a particle size distribution was created in order from the smallest particle size using the image analysis software, and the cumulative 50% particle size (D50) based on the number of particles was obtained for the particle size distribution. The results are shown in Tables 2 to 5.

[0077] (Piezoelectric constant) The piezoelectric constant d of each test piece 33 [pC / N], d 33 The measurements were taken using a meter (product name "ZJ-4B", manufactured by the Institute of Vocal Music, Chinese Academy of Sciences). The results are shown in Tables 2 to 5.

[0078] (Dielectric constant) The relative dielectric constant ε of each test piece 33 T / ε0 was calculated from the capacitance value at 1 kHz measured at room temperature using an impedance analyzer (HP4194A manufactured by Hewlett-Packard Co.). The results are shown in Tables 2 to 5.

[0079] (electromechanical coupling constant) The electromechanical coupling constant K of each test piece r was measured using an impedance analyzer (EYSIGHT, "E4990A"). The results are shown in Tables 2 to 5.

[0080] (Vice-Phase Analysis) A qualitative analysis of the subphases was performed on each test piece using an electron probe microanalyzer (EPMA) in the following manner. The polished surface (surface) of each test piece was photographed at a magnification of 5000 times, and the obtained images were used to perform elemental mapping of Ti (titanium), Zn (zinc), and Co (cobalt). The obtained elemental mapping images confirmed the presence of Ti, Zn, and Co in the subphases. In addition, the area ratio of the subphase to the parent phase was calculated from the backscattered electron image in an arbitrary field of view taken with a scanning electron microscope (SEM), and the ratio of the subphase was estimated by converting it into a volume. As a result, it was confirmed that the ratio was greater than 0 volume % and less than 10 volume %.

[0081] In addition, for each test piece, a peak analysis was performed based on a crystal phase database on the diffraction results of powder X-ray diffraction (XRD), and it was confirmed that the second crystal phase in all test pieces was a spinel compound.

[0082] [Table 1]

[0083] [Table 2]

[0084] [Examples 1 to 3, Comparative Examples 1 and 2] Table 2 summarizes the test results of Examples 1 to 3 and Comparative Examples 1 and 2. Fig. 3 is a graph summarizing the results of the piezoelectric constant and specific gravity of Examples 1 to 3 and Comparative Examples 1 and 2. The vertical axis on the left side of Fig. 3 represents the piezoelectric constant d 33 The vertical axis on the right side of Fig. 3 represents specific gravity [pC / N], and the horizontal axis on the right side of Fig. 3 represents the coefficient d of Ca in the composition formula of the first crystal phase (main phase). In all of Examples 1 to 3 and Comparative Examples 1 and 2, the firing temperature was 1000°C and the firing time was 100 hours.

[0085] The test pieces of Examples 1 to 3 had a Ca coefficient d of 0.02 or less, so that the specific gravity was 4.5 or more even at a firing temperature of 1000° C., and it was possible to perform a polarization treatment. From these results, it was confirmed that the test pieces of Examples 1 to 3 could be sintered even at a relatively low firing temperature of 1000° C.

[0086] In Comparative Example 2, the coefficient d of Ca is 0. In Example 1, the coefficient d of Ca is 0. As shown in FIG. 3, when d<0.004, the piezoelectric constant d 33 It was confirmed that the value of d dropped sharply. In the case of Comparative Example 2 (d=0), the specific gravity was high, but the piezoelectric constant was a low value of 128 pC / N. As shown in FIG. 3, when d=0.020, the piezoelectric constant d 33 The value was about 290 pC / N.

[0087] Comparative Example 1 is the case where d=0.036. In this case, it was confirmed that the specific gravity value (4.18) of the test piece was small and sintering was not possible. The test piece of Comparative Example 1 could not be polarized even after polarization treatment. Therefore, the result of the piezoelectric constant of Comparative Example 1 is not shown in the graph of FIG. 3.

[0088] As a result of a test carried out for reference, in the case of the same composition as in Comparative Example 1, sintering was possible when the firing temperature was 1100° C., and polarization by polarization treatment was also possible.

[0089] [Table 3]

[0090] [Examples 3 to 6] As shown in Table 1, each test piece of Examples 4 to 6 has the same composition as the test piece of Example 3. However, as shown in Tables 1 and 3, the sintering conditions (sintering time, sintering temperature) of Examples 4 to 6 are different from those of Example 3. Table 3 summarizes the test results of Examples 3 to 6. As shown in Table 3, in the case of Examples 4 to 8, it was confirmed that if the sintering temperature was 900 to 1000°C, the specific gravity became 4.4 or more with a sintering time of 1 hour, and sintering was possible.

[0091] [Table 4]

[0092] [Examples 2, 7, and 8] As shown in Table 1, each test piece of Examples 7 and 8 has the same composition as the test piece of Example 2. However, as shown in Tables 1 and 4, the firing conditions (firing time, firing temperature) of Examples 7 and 8 are different from those of Example 3. Table 4 summarizes the test results of Examples 2, 7, and 8. Figure 4 is a graph summarizing the results of the piezoelectric constant and specific gravity of Examples 2, 7, and 8. The vertical axis on the left side of Figure 4 is the piezoelectric constant d 33 The vertical axis on the right side of FIG. 4 represents the specific gravity [pC / N]. The horizontal axis of FIG. 4 represents the value r 50 [μm].

[0093] In the case of Example 2, Examples 7, and 8 (d = 0.007), the value of D50 in the particle size distribution of the first crystal phase, r 50 Even if [μm] is less than 0.68, d 33 It was confirmed that the value exceeded 100. As shown in the graph in Figure 4, d 33 value and D50 value (r 50 [μm]) is correlated with r 50 [μm] is 0.68 or more, d 33 Value improves.

[0094] [Table 5]

[0095] [Comparative Examples 2 to 4] As shown in Table 1, the test pieces of Comparative Examples 3 and 4 have the same composition as the test piece of Comparative Example 2. However, as shown in Tables 1 and 5, the firing conditions (firing time, firing temperature) of Comparative Examples 3 and 4 are different from those of Comparative Example 2. Table 5 summarizes the test results of Comparative Examples 2 to 4. FIG. 5 is a graph summarizing the results of the piezoelectric constants and specific gravities of Comparative Examples 2 to 4. The vertical axis on the left side of FIG. 5 represents the piezoelectric constant d 33 The vertical axis on the right side of FIG. 5 represents the specific gravity [pC / N]. The horizontal axis of FIG. 5 represents the value r 50 [μm].

[0096] In the cases of Comparative Examples 2 to 4 (when d = 0, that is, when d < 0.004), r 50 [μm] and d 33 There is no correlation between the values, e.g., r 50 Even if ≧0.68, d 33 The value is low, less than 100, and 50 Therefore, it can be said that the coefficient d of Ca in the composition formula (1) is preferably in the range of 0.004≦d≦0.020. [Explanation of symbols]

[0097] 10,200...piezoelectric element, 11,100...piezoelectric layer (piezoelectric ceramic layer), 12,13...internal electrodes, 14,15...external electrodes, 301,302...electrodes

Claims

1. A main phase formed of a first crystal phase made of an alkali niobate-based perovskite oxide; and a subphase including a second crystal phase made of an M-Ti-O spinel compound (element M is a monovalent to tetravalent metal element), The alkali niobate perovskite oxide is a lead-free piezoelectric composition represented by the following composition formula (1). (K a No b Li c Ca d C e ) f (D g E h )O i ・・・・・・(1) wherein element C is at least one of Sr and Ba, element D is at least one of Nb, Ti and Zr including at least Nb, element E is at least one of Fe, Co and Zn, a+b+c+d+e=1, 0.004≦d≦0.020, f is an arbitrary value, g+h=1, and i is an arbitrary value that can maintain a perovskite crystal structure.

2. The D50 value of the particle size distribution of the first crystal phase is r 50 The lead-free piezoelectric composition according to claim 1 , wherein [μm] is 0.57 or more.

3. The lead-free piezoelectric composition according to claim 1 or 2, which has a specific gravity of 4.4 or more.

4. A piezoelectric element having a structure in which the lead-free piezoelectric composition according to claim 1 or 2 and electrodes are alternately laminated.

Citation Information

Patent Citations

  • Unleaded piezoelectric ceramic composition, piezoelectric element using same, device, and method for manufacturing unleaded piezoelectric ceramic composition

    WO2014156015A1